Biomass reducing agent utilisation in rotary hearth furnace process for DRI production. (September 2015) - Han, H.; Duan, D.; Yuan, P.; Li, D.
Abstract : This study aims to provide a theoretical and technical basis for utilisation of biomass (bamboo char, charcoal and straw fibre) in the rotary hearth furnace process to produce direct reduced iron. Each biomass material has strengths and weaknesses. The bamboo char pellets possess high fixed carbon content, but the lower strength and the expansion rate of pellets make it difficult to reach production requirements. Although the charcoal based pellets are similar to coal based pellets, their strength is the lowest of these reducing agents. The straw fibre based pellets possess high strength and large volume shrinkage, but the low fixed carbon content results in low productivity. Using biomass in a combination of these alternatives can enable coal to be replaced and produce pellets with a higher metallization than with coal.